Effect of cumulative daunorubicin dose on cardiotoxicity after allogeneic stem cell transplantation. (October 2022) - Fujiwara, Shin-ichiro; Murahashi, Rui; Nakashima, Hirotomo; Matsuoka, Sae; Ikeda, Takashi; Toda, Yumiko; Ito, Shoko; Kawaguchi, Shin-ichiro; Nagayama, Takashi; Umino, Kento; Minakata, Daisuke; Morita, Kaoru; et al.
Abstract: Cardiotoxicity after allogeneic stem cell transplantation (SCT) is associated with a high rate of mortality and worsening quality of life. The relation between daunorubicin dose and post- allogeneic stem cell transplantation (SCT) cardiotoxicity remains unclear. We retrospectively evaluated 171 patients with acute myeloid leukemia (AML) who underwent their first allogeneic SCT at our institution between 2005 and 2021. High-dose daunorubicin (50 mg/m 2 /day for 5 days) and cytarabine were usually used as induction therapy for AML. The median cumulative daunorubicin dose was 310 mg/m 2 (range, 0–950 mg/m 2 ), and 43 patients received two courses of induction therapy with high-dose daunorubicin (daunorubicin doses of ≥500 mg/m 2 ). Cardiotoxicity developed in 12 patients, and the cumulative incidence at 2 years after SCT was 7.1%. Univariable analysis revealed that female sex, left ventricular ejection fraction (LVEF) of < 60% before SCT, and daunorubicin doses of ≥ 500 mg/m 2 were associated with cardiotoxicity. Multivariable analysis showed that a daunorubicin dose of ≥ 500 mg/m 2 was an independent risk factor for cardiotoxicity. LVEF decline during the study was observed with an increase in the daunorubicin dose, and only a daunorubicin dose of ≥ 500 mg/m2 was associated with a pre-SCT decreased LVEF. Second induction therapy with high-dose daunorubicin is a risk factor for cardiotoxicity after SCT. This should be taken into consideration when determining reinduction therapies for SCT-eligible patients with relapsed or refractory AML. Highlights: The cumulative incidence of cardiotoxicity at 2 years after SCT was 7.1%. Female, pre-SCT LVEF decline and daunorubicin dose were a risk for cardiotoxicity. Reinduction with high-dose daunorubicin increase the risk for cardiotoxicity.